2021
DOI: 10.1097/mcg.0000000000001482
|View full text |Cite
|
Sign up to set email alerts
|

Room for Improvement in the Treatment of Helicobacter pylori Infection

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 33 publications
4
18
0
3
Order By: Relevance
“…Triple M + L option should not be used as an alternative in case of a penicillin allergy or as a second-line therapy option. This is in line with our findings of suboptimal effectiveness of triple M + L in treatment-naive patients (66.7% by mITT) [24].…”
Section: Discussionsupporting
confidence: 93%
“…Triple M + L option should not be used as an alternative in case of a penicillin allergy or as a second-line therapy option. This is in line with our findings of suboptimal effectiveness of triple M + L in treatment-naive patients (66.7% by mITT) [24].…”
Section: Discussionsupporting
confidence: 93%
“…Leading international experts dictate the rules for the diagnosis of H. pylori infection; however, the majority of mistakes are still made when assessing the effectiveness of eradication, namely, the use of inadequate methods or lack of control. According to the European Registry on H. pylori management (Hp-EuReg), confirmation of the eradication was performed in 94% of the cases [43].…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, data from the European Registry on Helicobacter pylori management (Hp-EuReg) also showed that despite the high pretreatment clarithromycin resistance rate of 23% in Europe, the standard triple therapy containing both amoxicillin and clarithromycin remains as the most commonly prescribed (39%) H. pylori infection treatment, achieving only an 81.5% modified intention-to-treat eradication rate. 14,15 Therefore, in this study, we aimed to (1) review current first-line eradication regimens with a perprotocol eradication rate exceeding 90% in most geographic area, and (2) identify appropriate empirical H. pylori eradication strategies in regions with high and low clarithromycin resistances.…”
Section: Introductionmentioning
confidence: 99%